2020
DOI: 10.1371/journal.pone.0242154
|View full text |Cite
|
Sign up to set email alerts
|

Learning curve and performance in simulated difficult airway for the novel C-MAC® video-stylet and C-MAC® Macintosh video laryngoscope: A prospective randomized manikin trial

Abstract: Difficult airways can be managed with a range of devices, with video laryngoscopes (VLs) being the most common. The C-MAC® Video-Stylet (VS; Karl-Storz Germany), a hybrid between a flexible and a rigid intubation endoscope, has been recently introduced. The aim of this study is to investigate the performance of the VS compared to a VL (C-MAC Macintosh blade, Karl-Storz Germany) with regards to the learning curve for each device and its ability to manage a simulated difficult airway manikin. This is a single-ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 21 publications
2
12
0
Order By: Relevance
“…with VL in a normal airway vs. difficult airway due to limited mouth opening mannequin-based study. However, in the difficult airway model, VS was quicker to intubate [149,218]. Similar results were reported when VS was compared with DL [64,219,220].…”
Section: Application Of Vs Technique For Placement Of Double-lumen En...mentioning
confidence: 55%
“…with VL in a normal airway vs. difficult airway due to limited mouth opening mannequin-based study. However, in the difficult airway model, VS was quicker to intubate [149,218]. Similar results were reported when VS was compared with DL [64,219,220].…”
Section: Application Of Vs Technique For Placement Of Double-lumen En...mentioning
confidence: 55%
“…[ 35 ] Besides, there are specific situations where intubation with video-stylets may be advantageous over the conventional laryngoscopic approach such as difficulty in blade insertion in patients with limited oral opening [ 32 ] or the need for creating an unobstructed passageway through visualization of the vocal cords with video-stylets. [ 36 ] However, the latter does not guarantee an unobstructed path for tracheal tube insertion. [ 37 ] Although the operating principle of video-stylets is different from that of laryngoscopes, some authors reported that a steep learning curve can be achieved with video-stylets.…”
Section: Discussionmentioning
confidence: 99%
“…[ 37 ] Although the operating principle of video-stylets is different from that of laryngoscopes, some authors reported that a steep learning curve can be achieved with video-stylets. [ 36 , 38 ] Taking into account the increasing availability of video-stylets, [ 36 ] they may be incorporated into the difficult airway management algorithm to optimize patient care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, a variety of clinical scenarios including copious oral secretions, oropharyngeal bleeding, fogging caused by body temperature and gag reflex can be encountered in real-life clinical practice, but simulation cannot replicate these huge variations. [ 20 ]…”
Section: Challenges In Manikin/simulation-based Researchmentioning
confidence: 99%